Evaluation of dexmedetomidine as an adjuvant to low-concentration lidocaine/ropivacaine mixtures in ultrasound-guided axillary brachial plexus block - Qi Wang; Lu Feng (BMC Anesthesiology)
Abstract Background Dexmedetomidine (DEX) can be used with local anesthetics (LAs) to enhance the efficiency of a peripheral nerve block. However, there have been few studies on the combination of DEX and two different LAs for a brachial plexus block (BPB). The effects of adding DEX to low concentrations of lidocaine (LIDO) mixed with ropivacaine (ROP) on block onset, duration of anesthesia, and efficacy of analgesia in ultrasound-guided axillary (UGA) BPB were investigated. Methods The study protocol was approved by the Ethics Committee of the Second Affiliated Hospital of Harbin Medical University (ChiCTR-IPR-16007742, January 12, 2016), China. Seventy-five patients designated as American Society of Anesthesiologists Physical Status Classification System I or II and scheduled for forearm or hand surgery were assigned to three groups: (1) R group (n = 25), 0.25% ROP (30 mL) with 0.9% NaCl (3 mL); (2) RL group (n = 25), 0.25% ROP (15 ml) and 0.5% LIDO (15 mL) with 0.9% NaCl (3 mL); and (3) RLD group (n = 25), 0.25% ROP (15 ml) and 0.5% LIDO (15 mL) with DEX (0.75 µg/kg) (3 mL). Data on hemodynamic alterations, the bi-spectral index score (BIS), occurrence and timing of sensory and motor blocks, duration of analgesia, and requirement for rescue analgesia > 48 h were collected. Results The timings of the onsets of sensory and motor blocks were considerably reduced in the RL and RLD groups relative to the R group (p < 0.0001), with no substantial variation between the RL and RLD groups (p > 0.05). Compared with the R and RL groups, the analgesic and block periods in the RLD group were markedly increased (p < 0.0001). The requirement for flurbiprofen rescue intervention was markedly reduced in the RLD group relative to the R and RL groups (p < 0.0001). The BIS was markedly lower in the RLD group, between 20 and 60 min (p < 0.05). Conclusion The combination of ROP and LIDO led to a reduction in the onset time in UGA BPB. The addition of DEX to ROP/LIDO prolonged the duration of sensory and motor blocks. DEX also resulted in an extension of the analgesia time and provided significant sedation.